Improving Insurance Penetration in the Under-Developed Area with the Instrumentality of Third-Party Agents - Saka; Toyin, Shafau; Abere, (International Journal of Rehabilitation and Special Education (IJRSE), 2023)
This study examined the potential use of third-party agencies as a means of reaching  low-income rural earners with insurance offers and services. The people living in  the Ikorodu neighborhood received attention. Respondents were asked to complete  a questionnaire, and the information was then analyzed using the Logit Binary  Regression Model. According to the report, the most mitigating factors preventing the  expansion of insurance services among people living in rural areas are poverty and  illiteracy. This study came to the conclusion that marketing small goods insurance  (such as phones, televisions, etc.) and third-party agents through the operation of  insurance point of sale stands should be done in order to promote, develop, and  increase insurance in rural areas.
Keywords: Third-party Agency; Insurance Products and Services; Low-income Earners; Rural Areas